1-(2-Naphthyl)-2-(1-pyrrolidinyl)ethanone as a Photoinitiator for Methyl Methacrylate Polymerization - Dereli, Ummugulsum; Cakmak, Begum H.; Dogruyol, Sevnur Keskin (TECHNICAL ASSOC PHOTOPOLYMERS,JAPAN, 2019)
1-(2-Naphthyl)-2-(1-pyrrolidinypethanone (MPY) was synthesized as a photoinitiator for free radical polymerization and the structure was characterized by spectral analysis. MPY has ability to initiate the polymerization of methyl methacrylate (MMA) monomer in air upon irradiation. Absorption and fluorescence properties of this initiator are investigated and the singlet excited-state energy value calculated in dichloromethane. According to the results, MPY acts as a type 2 photoinitiator.
Keywords: Photoinitiator; Photopolymerization; Acetonaphthone; RADICAL POLYMERIZATION; REACTIVITY; PHOTOLYSIS; LIGHT; Polymer Science